Ocena stanu zdrowia podejrzanego w postępowaniu karnym - Żywucka-Kozłowska, Elżbieta (Studia Prawnoustrojowe, 2019)
The medical condition of human is the domain of medical science. This issue is also interesting for other fields of science. Psychology and law are an example. The assessment of human health is a complicated task. Specialists must have considerable knowledge to check the psychological state of the perpetrator and to eliminate the criminal liability of the perpetrator if the premises are preserved.